Table tennis: Cardiorespiratory and metabolic analysis of match and exercise in elite junior national players - Sperlich, B.; Koehler, K.; Holmberg, H. C.; Zinner, C.; Mester, J. (International Journal of Sports Physiology and Performance, 2011)
Purpose: The aim of the study was to determine the cardiorespiratory and metabolic characteristics during intense and moderate table tennis (TT) training, as well as during actual match play conditions. Methods: Blood lactate concentration (Lac), heart rate (HR, beats per minute [bpm]), oxygen uptake (VO2), and energy expenditure (EE) in 7 male participants of the German junior national team (age: 14 ± 1 y, weight: 60.5 ± 5.6 kg height; 165 ± 8 cm) were examined during six training sessions (TS) and during an international match. The VO2 was measured continuously with portable gas analyzers. Lac was assessed every 1 to 3 min during short breaks. Results: Mean (peak) values for Lac, HR, VO2, and EE during the TS were 1.2 ± 0.7 (4.5) mmol/L, 135 ± 18 (184) bpm, 23.5 ± 7.3 (43.0) mL/kg/min, and 6.8 ± 2.0 (11.2) METs, respectively. During match play, mean (peak) values were 1.1 ± 0.2 (1.6) mmol/L, 126 ± 22 (189) bpm, 25.6 ± 10.1 (45.9) mL/kg/min, and 4.8 ± 1.4 (9.6) METs, respectively. Conclusions: For the first time, cardiorespiratory and metabolic data in elite junior table tennis have been documented demonstrating low cardiorespiratory and metabolic demands during TT training and match play in internationally competing juniors.